Historical Biology - Historical Biology (Taylor & Francis, 2026)
Historical Biology is an international peer reviewed journal publishing papers covering evolutionary and systematic biology through time. The Journal is not limited by taxonomic group, publishing papers from human origins to the palaeobiology of the gigantic shark megalodon, to the latest developments in palaeobotany. The Journal accepts manuscripts on novel, theoretical, philosophical, and/or controversial topics, but also accepts so-called ‘negative results’ – as it is as important for the international community to know what does not work as what does.
FI 0.59
Q3
Keywords: Biological; Earth & Environmental Food Science; Acuerdos transformativos; Transformative agreements; Biología evolutiva; Paleobiología; Paleontología; Biodiversidad